Eksploitasi Nikel di Era Energi Terbarukan: Antara Harapan Global dan Kutukan Sumber Daya, Studi Kasus di Sulawesi Tenggara, Indonesia - Ham, Umirul; Abdillah, Ashar (CV WAHANA PUBLIKASI, 2025)
The transition toward renewable energy, promoted as a global response to the climate crisis, has generated a new paradox in Indonesia. On the one hand, green energy policies aim to reduce carbon emissions; on the other, they have accelerated the extraction of mineral resources such as nickel, leading to ecological degradation and social inequality. This study examines how the paradox of energy transition materializes in nickel exploitation practices in Southeast Sulawesi and to what extent this reflects the phenomenon of the resource curse. Using a descriptive qualitative approach within a socio-legal framework, the research integrates environmental law analysis with empirical data from interviews, observations, and policy documents. The findings reveal that weak law enforcement, overlapping institutional authority, and the dominance of economic interests have deepened ecological inequality. The green paradox and resource curse are evident in the imbalance between sustainability objectives and extractive realities. Addressing this issue requires environmental law reform based on ecological justice, strengthened multi-level governance, and meaningful community participation in decision-making processes.